From City Centres to Countryside: A Nationwide Study of Residence‑Based Inequities in Youth Physical Activity (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The aim was to investigate how self‑reported place of residence relates to multiple facets of physical activity behaviour in Finnish children, adolescents, and young adults.Methods: Analyses drew on the nationally representative Finnish School-Aged Physical Activity (LIITU in Finnish) monitoring study of 9‑ to 20‑year‑olds (n = 18,978). Respondents classified their residence with a four‑level scale (urban city centre, urban periphery, rural population centre, or dispersed rural area) and reported (1) adherence to the 60‑min‑per‑day moderate‑to‑vigorous physical activity (PA) guideline, (2) daily screen time, (3) sports club participation, (4) leisure-time PA, (5) active commuting to school or studies, (6) perceived physical functioning, and (7) perceived barriers to PA. Age‑ and sex‑specific prevalences were compared across residence categories using χ² tests (p < 0.05).Results: Urban upper secondary and high school students were more likely to meet the PA recommendation than their rural peers. Excessive screen time (>2 h/day) was slightly more common among rural primary school students compared to students in other residence areas. Active sports club participation was more common in urban areas compared to rural locations, with gaps of 20 percentage points in younger age groups. Active commuting was most prevalent in urban cores (80%) and rural centres (84%) and least common in the urban periphery (72%) and dispersed rural areas (71%). Rural youth reported more barriers, notably the absence of nearby facilities, organised instruction, and the high cost of participation. Perceived physical fitness was higher among urban than rural respondents, particularly from upper‑secondary age upwards.Conclusion: Residence strongly shaped many facets of PA behaviours such as organised sport involvement, active transport, perceived barriers to PA, and perceived physical functioning. The findings highlight geographical inequities – dispersed rural living is linked to fewer opportunities and greater obstacles to being active. Tailored policies are needed to ensure that all Finnish youth can achieve recommended PA levels.Support/Funding Source: The study was funded by the Finnish Ministry of Education and Culture.